2022
DOI: 10.4028/p-82d0o7
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study and Analysis of Modified Electromagnetic Band Gap in Frequency Notching of Ultra-Wide Band Antenna

Abstract: This paper presents parametric study of dual band notch ultra wideband (UWB) antenna using modified electromagnetic band gap. The Electromagnetic Band Gap (EBG) comprises of two strip patched and an edge-located via with respect to ground for dual notch band. The study was presented in order to have an improved knowledge of EBG characteristics and its effect on the notching band of a small squared ultra wideband antenna of size 24 by 31 mm2 dual band notch using HFSS software. The antenna operates within the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…It can be observed that most of these studies [28][29][30][32][33][34] could only notch two frequencies away from the UWB band. Only the study presented by the authors in [26] was able to notch three frequencies in line with the results presented in this paper. However, the bandwidth covered is relatively lower compared to the current study presented in this paper.…”
Section: Compared Performance Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…It can be observed that most of these studies [28][29][30][32][33][34] could only notch two frequencies away from the UWB band. Only the study presented by the authors in [26] was able to notch three frequencies in line with the results presented in this paper. However, the bandwidth covered is relatively lower compared to the current study presented in this paper.…”
Section: Compared Performance Analysissupporting
confidence: 88%
“…The novelty of the design lies in the combination of a modified EBG and a slot for frequency notching. This method successfully notched three frequencies with only two notching devices, unlike the conversionary method, which could notch only one frequency per notching device [24][25][26]. The analysis shown in this study revealed that a triple-band frequency notch could be achieved without degrading the performance of the antenna.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation